Preventing Loss of Independence through Exercise (PLIÉ) improves behavioral outcomes and increases default mode network connectivity in people with mild cognitive impairment: Developing topics. (7th December 2020) - Martinez, Steven; Barnes, Deborah E; Mehling, Wolf; Chesney, Margaret A; Lee, Jennifer Ann; Lee, Amanda; Chao, Linda L
Abstract: Background: Preventing Loss of Independence through Exercise (PLIÉ) is an integrative group movement program developed to improve quality of life and daily function in people with mild‐to‐moderate dementia. We performed a single‐arm pre‐post pilot trial to examine the impact of PLIÉ in people with mild cognitive impairment (MCI) on behavioral and neuroimaging outcomes. Methods: Study participants, recruited from the community, had received MCI diagnoses or reported subjective memory complaints plus Montreal Cognitive Assessment (MoCA) scores ≤ 26. PLIÉ classes were 1‐hour, 2 days/week over 12 weeks with 8‐12 participants per class. Pre‐post outcomes included validated measures of cognitive function, physical performance, self‐rated quality of life, mood, affect, mobility, social isolation, attention regulation, self‐regulation, and well‐being. Neuroimaging measures included structural magnetic resonance images (MRIs) and resting state fMRIs. Participants also completed PLIÉ satisfaction surveys. Standardized effect sizes (ES) were calculated based on pre‐post change divided by the baseline standard deviation, and paired t ‐tests were used to compare pre‐post scores. Changes in functional connectivity of the Default Mode Network (DMN) were examined using two nodes, the anterior medial prefrontal cortex (mPFC) and posterior cingulate cortex (PCC), as seeds. Results: Eighteen participants completed the 12‐week program. Participants were 74.9±9.1 years old (11 men, 7 women) and predominately white. Half were US‐veterans. We observed pre‐post improvement on measures of cognitive function (ES=0.33, p =0.001), physical performance (ES=0.39, p =0.047), social isolation (ES=0.62, p =0.009), and self‐regulation (ES=0.55, p =0.006). Though not statistically significant, most other measures suggested improvement with clinically meaningful effect sizes. Neuroimaging revealed increased functional connectivity between nodes of the DMN, specifically between the hippocampus and the mPFC ( p =.03) and between the PCC and bilateral parietal cortex after PLIÉ. Satisfaction ratings among participants were high (mean 3.95±.07; range 1‐4). Conclusion: These preliminary findings provide proof‐of‐concept for the PLIÉ intervention in people with MCI and suggest that it may enhance cognitive function, physical performance, mood and well‐being, and increase DMN functional connectivity. Additional studies with a control group are warranted.